2019
DOI: 10.1186/s12885-019-5686-1
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy detects metabolic signatures of radiation response and hypoxic fluctuations in non-small cell lung cancer

Abstract: Background Radiation therapy is a standard form of treating non-small cell lung cancer, however, local recurrence is a major issue with this type of treatment. A better understanding of the metabolic response to radiation therapy may provide insight into improved approaches for local tumour control. Cyclic hypoxia is a well-established determinant that influences radiation response, though its impact on other metabolic pathways that control radiosensitivity remains unclear. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
0
16
1
Order By: Relevance
“…Raman spectra are directly related to the biochemical composition of tissues [42][43][44] . In the past, Raman was used to detect metabolomic changes in different cancers 45,46 . However, Raman spectroscopy was never used before to study metabolomics in FSGS.…”
Section: Discussionmentioning
confidence: 99%
“…Raman spectra are directly related to the biochemical composition of tissues [42][43][44] . In the past, Raman was used to detect metabolomic changes in different cancers 45,46 . However, Raman spectroscopy was never used before to study metabolomics in FSGS.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of glycogen involves an array of complex signalling pathways, many of which can be directly related to tumour progression [8][9][10][11][12] . Increase in glycogen content within tumour cells post radiation treatment is thought to provide metabolic precursors which protect against hypoxia and other forms of stress 13 .…”
mentioning
confidence: 99%
“…Roman et al reported a change in the lipid composition and concentration in prostate cancer cells after X-ray radiation [ 80 ]. Similarly, metabolic alterations of cancer cells after radiation were also seen in nasopharyngeal cancer [ 79 ], non-small lung cancer [ 83 ], and glioblastoma [ 82 ]. A study by Milligan et al found different biochemical responses between radio-resistant and radio-sensitive cell types in lung (H460), breast (MCF7), and prostate (LNCaP) cells [ 81 ].…”
Section: Raman Spectroscopy As a Label-free Tool For Cancer Metabomentioning
confidence: 99%
“…Besides chemotherapy, radiotherapy is the mainstay of the treatment for a range of types of cancer. Monitoring radiation-induced cellular response of cancer at both cell and tissue levels was studied by Raman spectroscopy [79][80][81][82][83]. Roman et al reported a change in the lipid composition and concentration in prostate cancer cells after X-ray radiation [80].…”
Section: Cellular Responses To Anti-cancer Drugs and Radiotherapymentioning
confidence: 99%